An international study of technology enhanced learning-related strategies from the perspective of disruptive innovation. Issue 4 (12th August 2020) - Flavin, Michael; Quintero, Valentina
Abstract : Purpose: The purpose of this study was to analyse institutional strategy documents relating to technology-enhanced learning. Design/methodology/approach: In total, 84 documents were sampled from 71 leading higher education institutions (HEIs), identified through the Quacquarelli Symonds World University Rankings 2018. Qualitative content analysis with a directed approach was used to analyse the strategy documents. The specific theory used was disruptive innovation. The use of "innovation", or variants thereof, was counted in each document. Ten case studies from the sample were used for content analysis. Findings: Technology-enhanced learning-related strategy documents are conservative, advocating the more efficient use of existing technologies, or the incremental enhancement of existing technologies, but not transformation through technology. Originality/value: By evaluating the extent to which selected institutional strategies engage with innovation in technology-enhanced learning, this study argues HEIs advocate sustaining innovation or efficiency innovation to a greater extent than disruptive innovation.